Chemometric study on the electrochemical incineration of nitrilotriacetic acid using platinum and boron-doped diamond anode. (July 2015) - Zhang, Chunyong; He, Zhenzhu; Wu, Jingyu; Fu, Degang
Highlights: The performances of BDD and Pt are compared through a statistical approach. BDD and Pt show similar patterns towards NTA mineralization. Fractal geometry is initially employed in the field of EAOPs. The oxidation of NTA results in an increase in pH and a decreased in conductivity. NTA oxidation pathway is proposed. Abstract: This study investigated the electrochemical incineration of nitrilotriacetic acid (NTA) at boron-doped diamond (BDD) and platinum (Pt) anodes. Trials were performed in the presence of sulfate electrolyte media under recirculation mode. The parameters that influence the degradation efficiency were investigated, including applied current density, flow rate, supporting electrolyte concentration and reaction time. To reduce the number of experiments, the system had been managed under chemometric technique named Doehlert matrix. As a consequence, the mineralization of NTA demonstrated similar behavior upon operating parameters on these two anodes. Further kinetic study indicated that the degradations followed pseudo-first-order reactions for both BDD and Pt anodes, and the reaction rate constant of the former was found to be higher than that of the latter. Such difference could be interpreted by results from fractal analysis. In addition, a reaction sequence for NTA mineralization considering all the detected intermediates was also proposed.